2013
DOI: 10.1002/hyp.9838
|View full text |Cite
|
Sign up to set email alerts
|

A new longitudinal approach to assess hydrologic connectivity: Embanked floodplain inundation along the lower Mississippi River

Abstract: Abstract:Hydrologic connectivity is fundamental to understanding floodplain processes along meandering river corridors. This study contributes to understanding hydrologic connectivity by utilizing a high resolution Light Detection and Ranging DEM with a new GIS-based approach for identifying the precise elevation of flood stage. The method created a high-resolution longitudinal channel bank profile, enabling a detailed examination of embanked floodplain hydrologic connectivity. A simple channel crosssection ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…However, the 1D approach lacks the functionality for modelling complex, dynamic overland flow processes associated with the more frequent seasonal floods that are central in initiating floodplain connectivity during lower discharge flows (cf. Hudson et al, 2013). In contrast, TUFLOW explicitly models flow movement through multiple, intricately-connected overland flow pathways (Horritt and Bates, 2002), which is critical for capturing distributary and backwater flood pulses that occur with greater frequency.…”
Section: Floodplain Inundation Modellingmentioning
confidence: 99%
“…However, the 1D approach lacks the functionality for modelling complex, dynamic overland flow processes associated with the more frequent seasonal floods that are central in initiating floodplain connectivity during lower discharge flows (cf. Hudson et al, 2013). In contrast, TUFLOW explicitly models flow movement through multiple, intricately-connected overland flow pathways (Horritt and Bates, 2002), which is critical for capturing distributary and backwater flood pulses that occur with greater frequency.…”
Section: Floodplain Inundation Modellingmentioning
confidence: 99%
“…Moreover, in shallow lake-wetlands, the rate, duration and magnitude of water exchange between depressions and the adjacent main lake also have major influences on the water quality, aquatic habitat, organic matter and organisms, since movement of chemical constituents and biota are often associated with water flow [11][12][13]. Therefore, hydrological connectivity and water exchange are especially important considerations for shallow lake-wetlands [14,15]. A better understanding of these hydrologic processes is critical to helping regulate wetland structure and assess the status of vulnerable delta systems [1,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al (2011) reported 313 historically recorded breaches in artificially raised levees on the superelevated Yellow River in a 300 year period. Waters and sediment may spread via low bank points without main channel banks being fully overtopped except in the most extreme events (Hudson et al, 2013). Tributary channels may also significantly spread main channel sediment through the reversed flows that back up them from main rivers (Day et al, 2008).…”
Section: Sedimentation In Secondary Linear Systemsmentioning
confidence: 99%